Pemanfaatan Tembok Sekolah Dasar sebagai Mural Pendidikan Literasi: Utilization of Elementary School Walls as Literacy Education Murals - Wijayanti, Sri Hapsari; Khaqi, Rizal Bay; Feriyadi, Farhan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
As a form of participation of universities, which are members of LLDIKTI region III, for survivors of the eruption of Mount Semeru in Lumajang, East Java, a thematic community service program (KKNT)